A high-frequency high-impedance NiCuZn material and preparation method thereof
By accurately control the proportion of Nicuzn materials and the introduction of specific additives, combined with the process steps such as spray drying, the problem of the lattice deformation and grain grown up in the process of high -temperature sintering process is solved. Taking into account.
Patent Information
- Application Number
- CN202410945557.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-07-15
AI Technical Summary
The existing high-frequency and high-impedance NiCuZn materials are prone to lattice deformation and grain growth during high-temperature sintering, resulting in a decrease in thermal stability and affecting the durability and consistency of high-frequency performance.
By precisely controlling the proportion of the main components, introducing additives such as Co3O4, ZrB2 and VN, and using process steps such as spray drying, pre-calcination, secondary sand grinding and spray granulation, a product that can avoid lattice deformation and grain growth is prepared. High frequency and high impedance NiCuZn material.
It effectively improves the thermal stability of the material, maintains the excellence of high-frequency performance and the stability of magnetic properties, and avoids lattice deformation and grain growth.
Smart Images

Figure BDA0004945517200000081 
Figure BDA0004945517200000091 
Figure BDA0004945517200000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of magnetic materials, and in particular to a high-frequency and high-impedance NiCuZn material and a preparation method thereof. Background Art
[0002] High-frequency and high-impedance NiCuZn ferrite materials have important application value in the fields of electromagnetic wave shielding and electromagnetic interference suppression due to their unique electromagnetic properties. This material can not only effectively absorb and transform high-frequency electromagnetic waves, reduce the propagation and interference of electromagnetic waves, but also effectively reduce electromagnetic radiation, thereby improving the working stability and anti-interference performance of electronic equipment, which is of great significance for improving the performance and reliability of electronic equipment. Therefore, NiCuZn ferrite materials have become an indispensable magnetic material in modern electronic and communication technologies, and are widely used in wireless communications, radar systems, electromagnetic compatibility design and other fields.
[0003] However, the existing high-frequency and high-impedance NiCuZn materials will experience lattice deformation and grain growth during the high-temperature sintering process, which will reduce their thermal stability, affect the durability and consistency of high-frequency performance, and may also affect the magnetic properties of the material.
[0004] Therefore, there is an urgent need to develop a high-frequency, high-impedance NiCuZn material that can avoid lattice deformation and grain growth and has high thermal stability. Summary of the invention
[0005] In order to solve at least one of the above technical problems, a high-frequency, high-impedance NiCuZn material with high thermal stability that can avoid lattice deformation and grain growth is developed. The present application provides a high-frequency, high-impedance NiCuZn material and a preparation method thereof.
[0006] On the one hand, the present application provides a high-frequency high-impedance NiCuZn material, including a main component and an additive, wherein the main component includes 48.5-50.5 mol% Fe 2 O 3 , 21-24 mol% ZnO, 20-23 mol% NiO, the balance is CuO;
[0007] Based on the total weight of the main components, the additives include: 0.3-0.5wt% Co 3 O 4 、0.1~0.5wt%Al 2 O 3 , 0.1~0.5wt%ZrB 2 , 0.1~0.5wt%VN.
[0008] By adopting the above technical solution, the present application accurately controls the proportion of the main components, balances the magnetic properties and high-frequency properties of the material, and introduces specific additives to avoid lattice deformation and grain growth, thereby improving the thermal stability of the material.
[0009] Co 3 O 4 It can improve the anisotropy field of the material, enhance the stability at high frequencies, reduce the difference in thermal expansion coefficients, and thus improve thermal stability. 2 O 3 It can increase the volume resistivity of the material, reduce eddy current loss at high frequencies, and also refine the grains. 2 With high melting point and good chemical stability, as a grain boundary strengthening phase, it can effectively prevent grain growth, improve the mechanical strength of the material, and improve thermal stability. VN can effectively pin the grain boundary, inhibit grain growth, and improve the temperature resistance of the material, further improving thermal stability and mechanical properties.
[0010] This application Co 3 O 4 , ZrB 2 Together with VN, it inhibits grain growth, maintains the uniformity of the material's microstructure, and improves the thermal stability of the material.
[0011] Optionally, in terms of molar percentage, the main component includes: 49-50 mol% Fe 2 O 3 , 22~23mol% ZnO, 21~22mol% NiO, and the balance is CuO.
[0012] Optionally, based on the total weight of the main component, the additive includes: 0.35-0.45wt% Co 3 O 4 , 0.2~0.4wt%Al 2 O 3 , 0.2~0.4wt%ZrB 2 , 0.2~0.4wt%VN.
[0013] Optionally, the additive further comprises 0.1 to 0.5 wt % of modified chitosan, based on the total weight of the main components;
[0014] The modified chitosan is prepared from epichlorohydrin and chitosan, and the weight ratio of epichlorohydrin to chitosan is 0.1-0.4:1.
[0015] By adopting the above technical solution, the present application adds epichlorohydrin-modified chitosan, which can help to evenly disperse the main components and additives, promote the formation of finer and more uniform grains, thereby improving the microstructure and performance of the material, and can also improve the interface bonding between different components, reduce interface defects, and thus enhance the overall performance and thermal stability of the material.
[0016] In a second aspect, the present application provides a method for preparing the above-mentioned high-frequency high-impedance NiCuZn material, comprising the following steps:
[0017] S1, mixing the main components, adding deionized water, performing a sand milling, and spray drying to obtain a spray material; the sand milling time is 120 to 180 minutes;
[0018] S2, pre-burning the spray material to obtain a pre-burned material;
[0019] S3, adding the additive to the pre-sintered material, adding deionized water, adding 1.8wt% to 2.5wt% of PVA by weight of the pre-sintered material, and performing secondary sand grinding to obtain secondary sand abrasive;
[0020] S4, spraying and granulating the secondary abrasive material, and forming the abrasive material to obtain a ring blank;
[0021] S5. Sintering the ring blank to obtain a NiCuZn material.
[0022] By adopting the above technical solution, the preparation method adopted in this application can accurately control the microstructure of the material, thereby obtaining excellent high-frequency performance and thermal stability, and effectively avoiding lattice deformation and grain growth.
[0023] Primary sand grinding and spray drying can effectively reduce particle agglomeration and improve mixing uniformity. Pre-sintering can avoid lattice deformation and uneven grain growth. Adding additives and performing secondary sand grinding can further refine the particles. Additives can form grain boundary barriers, prevent grain growth, and effectively control grain size. Spray granulation can obtain particles with uniform shape and controllable particle size, which is convenient for subsequent molding processing. Sintering can make the material reach high density, optimize magnetic properties, and effectively control grain growth to maintain the stability of the material's microstructure.
[0024] Optionally, in the step S1, after adding deionized water, 0.01-0.1wt% of polyvinyl pyrrolidone based on the weight of the main component is also added; in the step S4, before spray granulation, 0.001-0.05wt% of polydimethylsiloxane based on the weight of the secondary sand abrasive is added.
[0025] By adopting the above technical solution, the addition of polyvinyl pyrrolidone in the present application can effectively prevent the agglomeration of particles during the grinding process, and also help to obtain a fine and uniform grain structure, thereby effectively avoiding lattice deformation and grain growth, and improving the thermal stability of the material.
[0026] The addition of polydimethylsiloxane in the present application can effectively reduce the friction between powders and improve their uniform dispersion; it can also prevent adhesion and agglomeration between particles, improve powder handling performance, and optimize the spray granulation effect.
[0027] Optionally, in step S2, the pre-firing temperature is 850-950°C.
[0028] By adopting the above technical solution, the pre-firing temperature of the present application can ensure that the raw materials react fully, remove moisture and impurities in the material, and improve the magnetic properties of the material. If the pre-firing temperature is too low, the reaction may be incomplete, and non-magnetic phases may exist, affecting the stability of the material; if the pre-firing temperature is too high, it may lead to over-sintering, affecting the microstructure and magnetic properties of the material.
[0029] Optionally, in step S3, the secondary sanding time is 30 to 80 minutes.
[0030] By adopting the above technical solution, the secondary sand milling of the present application can further refine and homogenize the particle size distribution of the powder, increase the density of the material and improve the magnetic properties.
[0031] Optionally, in step S3, the secondary sanding particle size distribution is: D50=0.6-1.0 μm.
[0032] By adopting the above technical solution, the secondary sand grinding particle size of the present application can effectively promote the formation of a more uniform microstructure of the material during the sintering process, which is beneficial to improving the magnetic properties while reducing magnetic losses.
[0033] Optionally, in step S4, the specifications of the ring blank are φ25×15×7.5 mm.
[0034] Optionally, in step S5, the sintering temperature is 1050-1100°C.
[0035] By adopting the above technical solution, the sintering temperature of the present application can densify the material and improve the mechanical strength and magnetic properties of the material. If the temperature is too low, it may lead to insufficient sintering, high internal porosity of the material, low mechanical strength, and poor magnetic properties; if the temperature is too high, it may lead to over-sintering, resulting in performance degradation, and even cracks, deformation and other problems.
[0036] In summary, the present invention includes at least one of the following beneficial technical effects:
[0037] 1. This application precisely controls the proportion of the main components, balances the magnetic properties of the material and improves the high-frequency impedance performance, and introduces specific additives to avoid lattice deformation and grain growth, thereby improving the thermal stability of the material.
[0038] 2. This application Co 3 O 4 , ZrB 2 Together with VN, it inhibits grain growth, maintains the uniformity of the material's microstructure, and improves the thermal stability of the material.
[0039] 3. The preparation method adopted in this application can accurately control the microstructure of the material, thereby obtaining excellent high-frequency performance and thermal stability, and effectively avoiding lattice deformation and grain growth. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a SEM image of the NiCuZn material obtained in Example 3;
[0041] Figure 2 This is the SEM image of the NiCuZn material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0042] The present application is further described in detail below with reference to the accompanying drawings and embodiments.
[0043] The present application designs a high-frequency high-impedance NiCuZn material, including a main component and an additive, in terms of molar percentage, the main component includes: 48.5-50.5 mol% Fe 2 O 3 , 21-24 mol% ZnO, 20-23 mol% NiO, the balance is CuO; based on the total weight of the main components, the additives include: 0.3-0.5 wt% Co 3 O 4 、0.1~0.5wt%Al 2 O 3 , 0.1~0.5wt%ZrB 2 , 0.1~0.5wt%VN.
[0044] The high-frequency and high-impedance NiCuZn material of the present application is prepared by the following method, including the following steps:
[0045] S1, mixing the main components, adding deionized water, performing a sand milling, and spray drying to obtain a spray material; the sand milling time is 120 to 180 minutes;
[0046] S2, pre-burning the spray material to obtain a pre-burned material;
[0047] S3, adding the additive to the pre-sintered material, adding deionized water, adding 1.8wt% to 2.5wt% of PVA by weight of the pre-sintered material, and performing secondary sand grinding to obtain secondary sand abrasive;
[0048] S4, spraying and granulating the secondary abrasive material, and forming the abrasive material to obtain a ring blank;
[0049] S5. Sintering the ring blank to obtain a NiCuZn material.
[0050] The applicant has designed the technical solution of the present application to solve the problems of lattice deformation and grain growth of existing NiCuZn materials during high-temperature sintering.
[0051] Firstly, the high-frequency and high-impedance NiCuZn material of the present application is proposed, which can avoid lattice deformation and grain growth and has high thermal stability.
[0052] Secondly, the preparation method of the high-frequency and high-impedance NiCuZn material adopted in this application can accurately control the microstructure of the material, thereby obtaining excellent high-frequency performance and thermal stability, and effectively avoiding lattice deformation and grain growth.
[0053] The raw materials used in this application are all from commercially available products, as follows:
[0054] Fe 2 O 3 : Purity 99.0%.
[0055] ZnO: purity 99.0%.
[0056] NiO: purity 99.0%.
[0057] CuO: purity 99.0%.
[0058] Co 3 O 4 : Purity 99.0%.
[0059] Al 2 O 3 : Purity 99.0%.
[0060] ZGar 2 : Purity 99.0%.
[0061] VN: Purity 99.0%.
[0062] PVA (polyvinyl alcohol): CAS: 9002-89-5.
[0063] Polyvinylpyrrolidone: CAS: 9003-39-8.
[0064] Polydimethylsiloxane: CAS: 9016-00-6.
[0065] Epichlorohydrin: CAS: 106-89-8.
[0066] Chitosan: CAS: 9012-76-4. Specific embodiments
[0068] Examples 1 to 5
[0069] Example 1
[0070] This embodiment provides a high-frequency high-impedance NiCuZn material, including a main component and an additive, in terms of molar percentage, the main component includes: 48.5 mol% Fe 2 O 3 , 24mol% ZnO, 20mol% NiO, the balance is CuO;
[0071] Based on the total weight of the main components, the additives include: 0.3wt% Co 3 O 4 、0.1wt%Al 2 O 3 , 0.5wt% ZrB 2 , 0.5wt%VN.
[0072] The preparation method comprises the following steps:
[0073] S1. Mix the main components, add deionized water, perform sand milling once, and spray dry to obtain a spray material; the sand milling time is 120 min;
[0074] S2, pre-burning the spray material at a pre-burning temperature of 900° C. to obtain a pre-burned material;
[0075] S3, adding additives to the pre-sintered material, adding deionized water, adding 1.8wt% of PVA by weight of the pre-sintered material, and performing secondary sand grinding to obtain secondary sand abrasive; the secondary sand grinding time is 55min; the secondary sand grinding particle size distribution is: D50=0.6μm;
[0076] S4, spray granulating and shaping the secondary abrasive to obtain a ring blank, the specification of which is φ25×15×7.5mm;
[0077] S5. Sintering the ring blank at a sintering temperature of 1075° C. to obtain a NiCuZn material.
[0078] Example 2
[0079] This embodiment provides a high-frequency high-impedance NiCuZn material, including a main component and an additive, in terms of molar percentage, the main component includes: 49 mol% Fe 2 O 3, 22mol% ZnO, 22mol% NiO, the balance is CuO;
[0080] Based on the total weight of the main components, the additives include: 0.45wt% Co 3 O 4 、0.4wt%Al 2 O 3 , 0.2wt% ZrB 2 , 0.2wt%VN.
[0081] The preparation method comprises the following steps:
[0082] S1. Mix the main components, add deionized water, perform sand milling once, and spray dry to obtain a spray material; the sand milling time is 135 min;
[0083] S2, pre-burning the spray material at a pre-burning temperature of 900° C. to obtain a pre-burned material;
[0084] S3, adding additives to the pre-sintered material, adding deionized water, adding 2.0wt% of PVA by weight of the pre-sintered material, and performing secondary sand grinding to obtain secondary sand abrasive; the secondary sand grinding time is 55min; the secondary sand grinding particle size distribution is: D50=0.6μm;
[0085] S4, spray granulating and shaping the secondary abrasive to obtain a ring blank, the specification of which is φ25×15×7.5mm;
[0086] S5. Sintering the ring blank at a sintering temperature of 1075° C. to obtain a NiCuZn material.
[0087] Example 3
[0088] This embodiment provides a high-frequency high-impedance NiCuZn material, including a main component and an additive, in terms of molar percentage, the main component includes: 49.5 mol% Fe 2 O 3 , 22.5mol% ZnO, 21.5mol% NiO, the balance is CuO;
[0089] Based on the total weight of the main components, the additives include: 0.4wt% Co 3 O 4 、0.3wt%Al 2 O 3 , 0.3wt% ZrB 2 , 0.3wt%VN.
[0090] The preparation method comprises the following steps:
[0091] S1. Mix the main components, add deionized water, perform sand milling once, and spray dry to obtain a spray material; the sand milling time is 150 min;
[0092] S2, pre-burning the spray material at a pre-burning temperature of 900° C. to obtain a pre-burned material;
[0093] S3, adding additives to the pre-sintered material, adding deionized water, adding 2.1wt% of PVA by weight of the pre-sintered material, and performing secondary sand grinding to obtain secondary sand abrasive; the secondary sand grinding time is 55min; the secondary sand grinding particle size distribution is: D50=0.6μm;
[0094] S4, spray granulating and shaping the secondary abrasive to obtain a ring blank, the specification of which is φ25×15×7.5mm;
[0095] S5. Sintering the ring blank at a sintering temperature of 1075° C. to obtain a NiCuZn material.
[0096] Example 4
[0097] This embodiment provides a high-frequency high-impedance NiCuZn material, including a main component and an additive, in terms of molar percentage, the main component includes: 50 mol% Fe 2 O 3 , 23mol% ZnO, 21mol% NiO, the balance is CuO;
[0098] Based on the total weight of the main components, the additives include: 0.35wt% Co 3 O 4 、0.2wt%Al 2 O 3 , 0.4wt% ZrB 2 , 0.4wt%VN.
[0099] The preparation method comprises the following steps:
[0100] S1. Mix the main components, add deionized water, perform sand milling once, and spray dry to obtain a spray material; the sand milling time is 165 min;
[0101] S2, pre-burning the spray material at a pre-burning temperature of 900° C. to obtain a pre-burned material;
[0102] S3, adding additives to the pre-sintered material, adding deionized water, adding 2.3wt% of PVA by weight of the pre-sintered material, and performing secondary sand grinding to obtain secondary sand abrasive; the secondary sand grinding time is 55min; the secondary sand grinding particle size distribution is: D50=0.6μm;
[0103] S4, spray granulating and shaping the secondary abrasive to obtain a ring blank, the specification of which is φ25×15×7.5mm;
[0104] S5. Sintering the ring blank at a sintering temperature of 1075° C. to obtain a NiCuZn material.
[0105] Example 5
[0106] This embodiment provides a high-frequency high-impedance NiCuZn material, including a main component and an additive, in terms of molar percentage, the main component includes: 50.5 mol% Fe 2 O 3 , 21mol% ZnO, 23mol% NiO, the balance is CuO;
[0107] Based on the total weight of the main components, the additives include: 0.5wt% Co 3 O 4 、0.5wt%Al 2 O 3 , 0.1wt% ZrB 2 , 0.1wt%VN.
[0108] The preparation method comprises the following steps:
[0109] S1. Mix the main components, add deionized water, perform sand milling once, and spray dry to obtain a spray material; the sand milling time is 180 min;
[0110] S2, pre-burning the spray material at a pre-burning temperature of 900° C. to obtain a pre-burned material;
[0111] S3, adding additives to the pre-sintered material, adding deionized water, adding 2.5wt% of PVA by weight of the pre-sintered material, and performing secondary sand grinding to obtain secondary sand abrasive; the secondary sand grinding time is 55min; the secondary sand grinding particle size distribution is: D50=0.6μm;
[0112] S4, spray granulating and shaping the secondary abrasive to obtain a ring blank, the specification of which is φ25×15×7.5mm;
[0113] S5. Sintering the ring blank at a sintering temperature of 1075° C. to obtain a NiCuZn material.
[0114] Comparative Examples 1 to 4
[0115] Comparative Example 1
[0116] The difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the additive does not contain Co 3 O 4 , ZrB 2 And VN.
[0117] Comparative Example 2
[0118] The difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the additive does not contain ZrB 2 and VN.
[0119] Comparative Example 3
[0120] The difference between Comparative Example 3 and Example 3 is that in Comparative Example 3, the additive does not contain ZrB 2 .
[0121] Comparative Example 4
[0122] The difference between Comparative Example 4 and Example 3 is that in Comparative Example 4, the additive does not contain VN.
[0123] Experimental testing
[0124] Test items and test methods
[0125] Micromorphology detection: Scanning electron microscope (SEM) and transmission electron microscope (TEM) were used to observe the micromorphology of NiCuZn materials, including whether the grain size is uniform, whether there is abnormal grain growth, and whether there is lattice deformation.
[0126] Initial magnetic permeability and impedance detection: Under the condition of turns N = 20Ts, the initial magnetic permeability μi and impedance value of NiCuZn material were detected by E4991A LCR tester.
[0127] Thermal stability test: The NiCuZn material was placed at 200°C for 300 hours, and the initial magnetic permeability reduction rate was tested to evaluate the thermal stability of the NiCuZn material.
[0128] The NiCuZn materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were tested for micromorphology, initial magnetic permeability, impedance and thermal stability. The test results are shown in Table 1.
[0129] Table 1
[0130]
[0131]
[0132] From the test results in Table 1, it can be seen that the NiCuZn materials prepared in Examples 1 to 5 have no lattice deformation and grain growth, and have high thermal stability.
[0133] Comparative Example 1 does not contain Co 3 O 4 , ZrB 2 And VN; Comparative Example 2 does not contain ZrB 2and VN; Comparative Example 3 does not contain ZrB 2 In Comparative Example 4, the additive does not contain VN, and the NiCuZn materials obtained in Comparative Examples 1 to 4 have lattice deformation and grain growth, and the thermal stability is significantly reduced.
[0134] Embodiments 6 to 16
[0135] Example 6
[0136] The difference between Example 6 and Example 3 is that in step S2 of Example 6, the pre-firing temperature is 850°C.
[0137] Example 7
[0138] The difference between Example 7 and Example 3 is that in step S2 of Example 7, the pre-firing temperature is 950°C.
[0139] Example 8
[0140] The difference between Example 8 and Example 3 is that in step S3 of Example 8, the secondary sanding time is 30 minutes.
[0141] Example 9
[0142] The difference between Example 9 and Example 3 is that in step S3 of Example 9, the secondary sanding time is 80 minutes.
[0143] Example 10
[0144] The difference between Example 10 and Example 3 is that in step S3 of Example 10, the secondary sanding particle size distribution is: D50=0.8 μm.
[0145] Embodiment 11
[0146] The difference between Example 11 and Example 3 is that in step S3 of Example 11, the secondary sanding particle size distribution is: D50=1.0 μm.
[0147] Example 12
[0148] The difference between Example 12 and Example 3 is that in step S5 of Example 12, the sintering temperature is 1050°C.
[0149] Example 13
[0150] The difference between Example 13 and Example 3 is that in step S5 of Example 13, the sintering temperature is 1100°C.
[0151] Embodiment 14
[0152] The difference between Example 14 and Example 10 is that in step S1 of Example 14, after adding deionized water, 0.01wt% of polyvinyl pyrrolidone based on the weight of the main component is also added; in step S4, before spray granulation, 0.001wt% of polydimethylsiloxane based on the weight of the secondary abrasive is added.
[0153] Embodiment 15
[0154] The difference between Example 15 and Example 14 is that in step S1 of Example 15, after adding deionized water, 0.05wt% of polyvinyl pyrrolidone based on the weight of the main component is also added; in step S4, before spray granulation, 0.02wt% of polydimethylsiloxane based on the weight of the secondary abrasive is added.
[0155] Example 16
[0156] The difference between Example 16 and Example 14 is that in step S1 of Example 16, after adding deionized water, 0.1wt% of polyvinyl pyrrolidone based on the weight of the main component is also added; in step S4, before spray granulation, 0.05wt% of polydimethylsiloxane based on the weight of the secondary abrasive is added.
[0157] The NiCuZn materials prepared in Examples 6 to 16 were tested for micromorphology, initial magnetic permeability, impedance and thermal stability. The test results are shown in Table 2.
[0158] Table 2
[0159]
[0160]
[0161]
[0162] From the test results in Table 2, it can be seen that among Examples 6, 7 and 3, the NiCuZn material prepared in Example 3 has the highest thermal stability.
[0163] Among Example 8, Example 9 and Example 3, the NiCuZn material prepared in Example 3 has the highest thermal stability.
[0164] Among Example 10, Example 11 and Example 3, the NiCuZn material prepared in Example 10 has the highest thermal stability.
[0165] Among Example 12, Example 13 and Example 3, the NiCuZn material prepared in Example 3 has the highest thermal stability.
[0166] The NiCuZn material prepared in Example 14 has improved thermal stability compared with that in Example 10; among Examples 14 to 16, the NiCuZn material prepared in Example 15 has the highest thermal stability.
[0167] Embodiments 17 to 19
[0168] Embodiment 17
[0169] The difference between Example 17 and Example 15 is that the additive of Example 17 also includes 0.1wt% of modified chitosan based on the total weight of the main components, and the preparation method of the modified chitosan is: dissolving chitosan in 3% acetic acid solution; adding epichlorohydrin, stirring, and reacting at 60°C for 12h; filtering, washing, and drying to obtain modified chitosan; wherein the weight ratio of epichlorohydrin to chitosan is 0.3:1.
[0170] Embodiment 18
[0171] The difference between Example 18 and Example 17 is that in Example 18, the weight fraction of the modified chitosan is 0.3 wt % of the total weight of the main components.
[0172] Embodiment 19
[0173] The difference between Example 19 and Example 17 is that in Example 19, the weight fraction of the modified chitosan is 0.5wt% of the total weight of the main components.
[0174] The NiCuZn materials prepared in Examples 17 to 19 were tested for micromorphology, initial magnetic permeability, impedance and thermal stability. The test results are shown in Table 3.
[0175] Table 3
[0176]
[0177] From the test results in Table 3, it can be seen that the thermal stability of the NiCuZn material prepared in Example 17 is improved compared with that in Example 15; among Examples 17 to 19, the thermal stability of the NiCuZn material prepared in Example 18 is the highest.
[0178] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A high-frequency high-impedance NiCuZn material, characterized in that: It comprises a main component and an additive, wherein, by molar percentage, the main component comprises: 48.5-50.5 mol% Fe2O3, 21-24 mol% ZnO, 20-23 mol% NiO, and the balance is CuO; Based on the total weight of the main components, the additives include: 0.3-0.5wt% Co3O4, 0.1-0.5wt% Al2O3, 0.1-0.5wt% ZrB2, and 0.1-0.5wt% VN.
2. The high-frequency high-impedance NiCuZn material according to claim 1, characterized in that: In terms of molar percentage, the main components include: 49-50 mol% Fe2O3, 22-23 mol% ZnO, 21-22 mol% NiO, and the balance is CuO.
3. The high-frequency high-impedance NiCuZn material according to claim 1, characterized in that: Based on the total weight of the main components, the additives include: 0.35-0.45wt% Co3O4, 0.2-0.4wt% Al2O3, 0.2-0.4wt% ZrB2, and 0.2-0.4wt% VN.
4. The high-frequency high-impedance NiCuZn material according to claim 1, characterized in that: Based on the total weight of the main components, the additive further includes 0.1-0.5wt% modified chitosan; The modified chitosan is prepared from epichlorohydrin and chitosan, and the weight ratio of epichlorohydrin to chitosan is 0.1-0.4:
1.
5. A method for preparing the high-frequency high-impedance NiCuZn material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing the main components, adding deionized water, performing a sand milling, and spray drying to obtain a spray material; the sand milling time is 120-180 min; S2, pre-burning the spray material to obtain a pre-burned material; S3, adding the additive to the pre-sintered material, adding deionized water, adding 1.8wt% to 2.5wt% of PVA by weight of the pre-sintered material, and performing secondary sand grinding to obtain secondary sand abrasive; S4, spraying and granulating the secondary abrasive material, and forming the abrasive material to obtain a ring blank; S5. Sintering the ring blank to obtain a NiCuZn material.
6. The method for preparing the high-frequency and high-impedance NiCuZn material according to claim 5, characterized in that: In the step S1, after adding deionized water, 0.01-0.1wt% of polyvinyl pyrrolidone based on the weight of the main component is also added; in the step S4, before spray granulation, 0.001-0.05wt% of polydimethylsiloxane based on the weight of the secondary sand abrasive is added.
7. The method for preparing the high-frequency and high-impedance NiCuZn material according to claim 5, characterized in that: In the step S2, the pre-firing temperature is 850-950°C.
8. The method for preparing the high-frequency and high-impedance NiCuZn material according to claim 5, characterized in that: In step S3, the secondary sanding time is 30 to 80 minutes.
9. The method for preparing the high-frequency and high-impedance NiCuZn material according to claim 5, characterized in that: In the step S3, the secondary sand grinding particle size distribution is: D50=0.6~1.0μm.
10. The method for preparing high-frequency and high-impedance NiCuZn material according to claim 5, characterized in that: In the step S5, the sintering temperature is 1050-1100°C.
Citation Information
Patent Citations
NiCuZn ferrite material, preparation method thereof and laminated sheet-type magnetic bead
CN105036724A
NiCuZn Ferrite material and preparation method and application thereof
CN107619271A